ISSEMINATED SUPERFICIAL ACTINIC POROKERATOSIS IN PATIENT SUFFERING FROM PLAQUE PSORIASIS: A CASE REPORT - L. F. Znamenskaya; V. V. Chikin; I. A. Kappusheva; V. V. Kondrasheva (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Monitoring of disseminated superficial actinic porokeratosis (DSAP) in patient suffering from plaque psoriasis treated by PUVA therapy was presented. DSAP is a rare skin disease developing in the result of keratosis disorder caused by solar radiation and appearing as clearly localized ringed or line plates. As patients with DSAP are sensitive to solar radiation, phototherapy is contraindicated for them. In this regard, subcutaneous injections of Methotrexate 10 mg once a week were prescribed to a patient suffering from psoriasis. Psoriatic rashes were regressed after the second injection, instead of them DSAP rashes remained.